HUMANITARIAN INNOVATIONS IN THE SPACE-TIME DIMENSION OF THE INFORMATION SOCIETY - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
The problem of the constitution of the humanitarian innovations as parts of modern culture is devoted